Van Siantar's Bandietsabram Christopher Postcolonial Study on Novel - Yusni Khairul Amri; Hasan Al Gaffari (Budapest International Research and Critics University, 2022)
This study aims to describe the hybridity and mimicry analysis of Abram Christopher Sinaga's novel Bandiet-Bandiet Van Siantar with a postcolonial approach. The data source for this research is Abram Christopher Sinaga's 236-page novel Bandiet-Bandiet Van Siantar published by Obelia Publisher in Medan, first printing in June 2021. The data for this research is an overview of the hybridity and mimicry of Abram Christopher Sinaga's novel Van Siantar Bandies. This research method uses descriptive method by collecting data, describing data, and analyzing data. The instrument used in this study is a documentation guide. The data analysis technique used is to read the novel repeatedly, to appreciate, to understand, to collect data, to underline, to describe and to conclude the research results. The results of this study found that the form of hybridity in the form of resistance was obtained as much as 10 data and hybridity regarding without coercion obtained as much as 5 data. Furthermore, mimicry or imitation using colonial language obtained as much as 5 data, mimicry in the form of living equipment as much as 2 data, mimicry in the form of livelihood as much as 4 data, and mimicry in the form of knowledge as much as 3 data.